Understanding the roles of rhetorical devices and intertextuality in promotional discourse - Zulkipli, Muhammad Fakhrullah; Ariffin, Adlina (Global Academic Excellence, 2019)
This paper examines the interplay of rhetorical devices and intertextuality in projecting the branding image of promotional discourse i.e. online advertisements of three common fast food chains in Malaysia. This study, which adapted the framework of rhetorical devices developed by Michalik and Michalska-Suchanek (2016), investigated the utilisation of rhetorical devices and intertextual elements in the advertisements by McDonald's, Kentucky Fried Chicken (KFC) and Texas Chicken. The findings from the study show that there is a great difference in the use of the rhetorical devices by the three fast food chains where Texas Chicken employed the highest number in the types of devices (9 out of 14 types) and KFC utilized the least elements (4 out of 14 types). Halal logo is also used as a common rhetorical device in the advertisements to exert the permissibility/halalness of the food. An examination on the intertextuality of the advertisements brings to light the crucial use of pop culture and local socio-cultural elements in promotional discourse. It could be deduced from the study that among the factors that shape the advertisements are product reputation, modern popular culture, consumers’ beliefs and cultural norms.